Utilization of Acoustic Wave Velocity for Permeability Estimation in Static Reservoir Modeling: A Field Case - Suryo Prakoso; Muhammad Burhannudinnur; Teddy Irano; Firman Herdiansyah (Graduate Program of Syiah Kuala University, 2021)
Several researches have shown that P-wave velocity carries information on the complexity of the rock's pore geometry and pore structure. Their complexity can be characterized by critical porosity. Therefore, the P-wave velocity is used to estimate permeability. This research uses data taken from the Tomori formation from Banggai-Sula basin, Central Sulawesi, which is a carbonate rock reservoir. Also, this research aims to obtain a 3D permeability model by using acoustic wave velocity cube data. The results show that permeability can be modeled well using acoustic wave velocity data. Furthermore, compared to the raw data log of permeability, the modeling results using wave velocity based on critical porosity show good results. This method is another alternative to permeability modeling if acoustic wave velocity cube data is available